2016
DOI: 10.2197/ipsjjip.24.598
|View full text |Cite
|
Sign up to set email alerts
|

Pain Level Detection From Facial Image Captured by Smartphone

Abstract: Accurate symptom of cancer patient in regular basis is highly concern to the medical service provider for clinical decision making such as adjustment of medication. Since patients have limitations to provide self-reported symptoms, we have investigated how mobile phone application can play the vital role to help the patients in this case. We have used facial images captured by smart phone to detect pain level accurately. In this pain detection process, existing algorithms and infrastructure are used for cancer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 34 publications
0
13
0
Order By: Relevance
“…Combining movement quality with pain level evaluation-Patients' pain level during a rehabilitation exercise session can reflect their health status, and thus, it can be an important indicator of the treatment outcome. Accordingly, a great deal of study focused on assessing pain level [109], [110], [112], [165], [166]. E.g., in [110] facial images captured by a smartphone were used to estimate the pain level of cancer patients.…”
Section: Future Directionsmentioning
confidence: 99%
See 1 more Smart Citation
“…Combining movement quality with pain level evaluation-Patients' pain level during a rehabilitation exercise session can reflect their health status, and thus, it can be an important indicator of the treatment outcome. Accordingly, a great deal of study focused on assessing pain level [109], [110], [112], [165], [166]. E.g., in [110] facial images captured by a smartphone were used to estimate the pain level of cancer patients.…”
Section: Future Directionsmentioning
confidence: 99%
“…Accordingly, a great deal of study focused on assessing pain level [109], [110], [112], [165], [166]. E.g., in [110] facial images captured by a smartphone were used to estimate the pain level of cancer patients. Milton et al [165] studied the relation between common symptoms and health aspects, and found that the pain intensity produces stronger relationships when compared to other symptoms.…”
Section: Future Directionsmentioning
confidence: 99%
“…The main challenge in studies related to pain is the establishment of a ground truth with reliable labels. A novel approach to collect data was suggested in the study of Hasan et al [82], where they collected images and self-reported levels of pain by patients using a mobile app. While the use of mobile apps could ease the data collection process, special attention should be given to the reliability of data and ethical concerns which might raise from them.…”
Section: Table I Homology Of Pain Expression Across the Lifespanmentioning
confidence: 99%
“…Predicted pain level range was also the same as input pain level 0-10 where 0 means no pain and 10 means the highest level of pain. Then the range of pain level (0-10) was transformed into three (3) categorical levels: low (0-3), mid (4-6) and high (7)(8)(9)(10). This classification into categories is similar to the Brief Pain Inventory which has been proposed and validated across different cultures [29].…”
Section: Cross-sectional Evaluationmentioning
confidence: 99%
“…Assessment of pain is an important step towards the treatment of pain. There is a need for manageable, valid and reliable tools to assess pain [10]. Accurate assessment of pain is critical for the identification of appropriate interventions and for evaluating the effectiveness of such interventions in the clinical setting [11].…”
Section: Introductionmentioning
confidence: 99%